Օրենսդրական գործընթացի բարեփոխումներն ըստ 2015թ. սահմանադրական փոփոխությունների - Մարտին Մանուկյան (ՀՀ ԳԱԱ հրատ.)
В Республике Армения 6 декабря 2015 г. посредством выборов произошли содержательные и знаменательные поправки в структуре Конституции РА. This article presents in short the substantial changes fulfilled in content and volume in the Constitution of RA on 6 December 2015 after a majority approval in the referendum.
Keywords: Law